2008
DOI: 10.1051/0004-6361:200809956
|View full text |Cite
|
Sign up to set email alerts
|

High variability in Vela X-1: giant flares and off states

Abstract: Aims. We investigate the spectral and temporal behavior of the high mass X-ray binary Vela X-1 during a phase of high activity, with special focus on the observed giant flares and off states. Methods. INTEGRAL observed Vela X-1 in a long almost uninterrupted observation for two weeks in 2003 Nov/Dec. The data were analyzed with OSA 7.0 and FTOOLS 6.2. We derive the pulse period, light curves, spectra, hardness ratios, and hardness intensity diagrams, and study the eclipse. Results. In addition to an already hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
246
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(274 citation statements)
references
References 78 publications
28
246
0
Order By: Relevance
“…Later observations failed to detect this low energy feature, revealing only one absorption line at 53 ∼ 55 keV (Orlandini et al 1998;La Barbera et al 2003;Kreykenbohm et al 2008). Kretschmar et al (1997), with HEXE, Kreykenbohm et al (2002) with RXTE, Schanne et al (2007) with INTEGRAL, and Maitra & Paul (2013) and Odaka et al (2013) with Suzaku confirmed the presence of both features, with energies varying between ∼ 23 keV and ∼ 27 keV and between ∼ 45 keV and ∼ 54 keV, respectively.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Later observations failed to detect this low energy feature, revealing only one absorption line at 53 ∼ 55 keV (Orlandini et al 1998;La Barbera et al 2003;Kreykenbohm et al 2008). Kretschmar et al (1997), with HEXE, Kreykenbohm et al (2002) with RXTE, Schanne et al (2007) with INTEGRAL, and Maitra & Paul (2013) and Odaka et al (2013) with Suzaku confirmed the presence of both features, with energies varying between ∼ 23 keV and ∼ 27 keV and between ∼ 45 keV and ∼ 54 keV, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…The mean luminosity of the source is 5 × 10 36 erg s −1 (Fürst et al 2010), and the flux shows a great variability even at short time scales (hours), with the source going from off-states to giant flares up to a few Crab (Kreykenbohm et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We will refer to these non-detections as "off-states" or "dips", regardless of the cause of diminished flux (similarly to the definition assumed by Kreykenbohm et al 2008, who studied a subsample of INTEGRAL data of Vela X-1, at early times of the mission).…”
Section: Resultsmentioning
confidence: 99%
“…Located at a distance of 1.9 kpc (Sadakane et al 1985), the orbital period of the system is 8.96 d (van Kerkwijk et al 1995, Kreykenbohm et al 2008, implying that the neutron star orbit is embedded in the companion wind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation